2017
DOI: 10.1016/j.jpeds.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index in Infancy May Predict Severe Obesity in Early Childhood

Abstract: Objective To characterize growth trajectories of children who develop severe obesity by age 6 years and identify clinical thresholds for detection of high-risk children before the onset of obesity. Study design Two lean (body mass index [BMI] 5th to ≤75th percentile) and 2 severely obese (BMI ≥99th percentile) groups were selected from populations treated at pediatric referral and primary care clinics. A population-based cohort was used to validate the utility of identified risk thresholds. Repeated-measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 14 publications
2
34
0
3
Order By: Relevance
“…Accelerated growth during infancy and increased BMI in early life are known to enhance the risk for obesity [289,290,291], T2DM [292,293], allergy [294,295,296] and cancer later in life [297,298,299]. …”
Section: Milk-mediated Epigenetic Signaling and Diseases Of Civilmentioning
confidence: 99%
“…Accelerated growth during infancy and increased BMI in early life are known to enhance the risk for obesity [289,290,291], T2DM [292,293], allergy [294,295,296] and cancer later in life [297,298,299]. …”
Section: Milk-mediated Epigenetic Signaling and Diseases Of Civilmentioning
confidence: 99%
“…In children, the relation between body mass index (BMI) and adiposity varies with age and sex, so BMI thresholds are usually defined in terms of specific centiles on a growth reference curve [6]. Extremely high BMI values considerably increase children’s physical and mental health risks [7-11]. When compared with children with overweight or obesity, who often do not experience visible morbidities during childhood, children with severe obesity frequently have immediate health consequences, including a worse cardiometabolic risk profile, earlier signs of vascular dysfunction, and subclinical atherosclerosis [12-23].…”
Section: Introductionmentioning
confidence: 99%
“…Although the report for the CDC growth charts (Kuczmarski et al, 2002) cautioned about extrapolating outside the 3rd and 97th percentiles of BMI, BMI z remains widely used in studies that include large numbers of children with very high BMIs (Hampl et al, 2016; Kreier et al, 2013; McCormick et al, 2014; Smego et al, 2017; Wang et al, 2015). We have shown that, among children with severe obesity, BMI z levels are only weakly associated with other measures of body size (Freedman et al, 2017a) and the current results highlight the drawbacks of attempting to assess longitudinal BMI z changes.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolated z -scores based on the CDC growth charts are widely used among children who have very high BMIs (Baughcum et al, 2015; Hampl et al, 2016; Kreier et al, 2013; Smego et al, 2017; Wang et al, 2015). However, BMI z values for extremely high BMIs can differ substantially from the empirical estimates (Flegal et al, 2009), have an effective upper limit (Woo, 2009) and are strongly influenced by sex and age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation